Veterinary care of sick and injured mallards. Issue 7 (17th July 2014) - Bexton, Steve; Couper, David
Abstract : Mallards (Anas platyrynchus) are found throughout the Northern hemisphere. Their adaptability to different habitats means they often live in proximity to humans, putting them at increased risk from man‐made hazards. Sick and injured mallards are regularly rescued and taken to veterinary practices; they are tolerant of captivity and relatively easy to care for, making them ideal candidates for rehabilitation. The minimum required of a veterinary surgeon is to provide first aid care and alleviate suffering before transferring them to a local wildlife rehabilitator. This article describes some of the common conditions seen in mallards and how veterinary surgeons can best care for and treat them.